Integrative revision of the Iberian species of Coscinia Hübner, [1819] sensu lato and Spiris Hübner, [1819], (Lepidoptera: Erebidae, Arctiinae) - Macià, Ramon; Mally, Richard; Ylla, Josep; Gastón, Javier; Huertas, Manuel (Zootaxa, 2019)
The Iberian species of the genera Coscinia Hübner, [1819] and Spiris Hübner, [1819], as well as three other species from the Mediterranean area, are revised based on morphological and molecular genetic data. Our results suggest the separation into four morphologically and phylogenetically different genera: Coscinia Hübner, [1819], Lerautia Kemal & Koçak, 2006 stat. rev., Sagarriella Macià, Mally, Ylla, Gastón & Huertas gen. nov. and Spiris Hübner, [1819]. We conclude that there are eight species of the Coscinia genus group present in the studied area: Coscinia cribraria (Linnaeus, 1758), Coscinia chrysocephala (Hübner, [1810]) stat. rev., Coscinia mariarosae Expósito, 1991, Sagarriella libyssa caligans (Turati, 1907) comb. nov., Sagarriella romei (Sagarra, 1924) (= romeii sensu auctorum) comb. nov., Spiris striata Hübner, [1819], Spiris slovenica (Daniel, 1939) and Lerautia bifasciata (Rambur, 1832) comb. rev. We consider Coscinia cribraria benderi (Marten, 1957) stat. nov., Coscinia c. rippertii (Boisduval, 1834) and Coscinia c. ibicenca Kobes, 1991 stat. rev. to be subspecies of C. cribraria. COI Barcodes of C. cribraria diverge by up to 7.99%, and the investigated specimens group into six different COI Barcode BINs. Both the phylogenetic analysis of mitochondrial and nuclear DNA and the morphological examination of different specimens corroborate the changes in taxonomic status and justify the proposed taxonomic categories. We present images of adults and genitalia of both sexes, the immature stages of some of the species and the subspecies studied, as well as phylogenetic results from the analysis of genetic data. We also include data on life history, foodplants and geographical distribution.